Pelatihan Penyusunan Evaluasi Pembelajaran Bahasa Arab Berbasis Ranah Kognitif Taksonomi Bloom di SMP Islam Brawijaya Pungging Mojokerto - Khoirunnisa’il Fitriyah; Dwi Ajeng Sura Wasiah (BADAN PENERBIT STIEPARI PRESS, 2025)
This Community Service (PKM) activity aims to improve the competence of Arabic teachers at SMPI Brawijaya Pungging Mojokerto in compiling learning evaluations based on the cognitive domain in accordance with Bloom's Taxonomy. So far, learning evaluations often only focus on aspects of low-level knowledge (lower-order thinking skills), while high-level thinking skills (higher-order thinking skills) have not been systematically touched upon. Through this training, teachers are introduced to the concept of Bloom's Taxonomy as a whole, from the level of knowledge to evaluation, and are guided to compile indicators, learning objectives, and Arabic evaluation instruments that are in line with each level of the cognitive domain. The method of implementing the activity includes delivering materials, interactive discussions, and practicing compiling evaluations based on Bloom's Taxonomy. The results of the activity show an increase in teachers' understanding and skills in designing evaluations that are more varied, contextual, and able to encourage students' critical thinking skills. This activity is expected to be the first step in improving the quality of Arabic learning as a whole at SMPI Brawijaya Pungging Mojokerto.